Tanggung Jawab Negara Terhadap Hak Masyarakat Hukum Adat di Pulau Rempang dalam Perspektif HAM - Earlene, Felishella; Sitabuana, Tundjung Herning (Diploma IV Pertanahan Sekolah Tinggi Pertanahan Nasional, 2024)
The Indonesian constitution and international instruments mandate the recognition and protection of customary law communities. The plan to build the Rempang Eco-City on Rempang Island triggered an agrarian conflict, which resulted in violations of the traditional rights of the Rempang Island customary community, especially land rights. This research is intended to determine the state's responsibility for the rights of the Rempang Island customary community by examining it from a Human Rights (HAM) perspective. This research uses a type of normative legal research with descriptive research characteristics through data collection techniques, a literature study of secondary data through a statutory regulations approach, and is analyzed qualitatively. This legal research provides results that implementing development must be based on the human rights of local customary law communities in order to reduce the potential for conflict, considering that human rights are very closely related to development, and there is a contradiction between fulfilling rights through the implementation of National Strategic Projects (PSN) in order to improve the quality of life of the community. Local communities' traditional rights serve as a foundation for state accountability, ensuring the fulfillment of their human rights through relocation efforts, all while respecting and safeguarding their right to remain free from forced relocation. Masyarakat hukum adat telah diakui dan dilindungi sebagaimana diamanatkan dalam konstitusi Indonesia maupun melalui instrumen internasional. Rencana pembangunan Rempang Eco-City di Pulau Rempang memicu konflik agraria yang mengakibatkan pelanggaran hak-hak tradisional masyarakat hukum adat Pulau Rempang khususnya hak atas tanah. Penelitian ini ditujukan guna mengetahui tanggung jawab negara atas hak masyarakat hukum adat Pulau Rempang dengan mengkaji dari perspektif Hak Asasi Manusia (HAM). Penelitian ini menggunakan jenis penelitian hukum normatif dengan sifat penelitian deskriptif melalui teknik pengumpulan data studi kepustakaan terhadap data sekunder melalui pendekatan peraturan perundang-undangan, dan dianalisis secara kualitatif. Penelitian hukum ini memberikan hasil bahwa dalam melaksanakan pembangunan harus berlandaskan pada HAM masyarakat hukum adat setempat agar mengurangi potensi terjadinya konflik mengingat HAM memiliki kaitan sangat erat dengan pembangunan, dan terdapat kontradiksi antara pemenuhan hak melalui pelaksanaan Proyek Strategis Nasional (PSN) guna meningkatkan kualitas hidup masyarakat dengan hak tradisional masyarakat setempat, serta bentuk pertanggungjawaban negara dalam pemenuhan HAM masyarakat setempat ialah melalui upaya relokasi dengan tetap menghormati dan melindungi hak untuk tidak direlokasi secara paksa.